2004
DOI: 10.1016/j.jfca.2003.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the biotin content of select foods using accurate and sensitive HPLC/avidin binding

Abstract: Assessing dietary biotin content, biotin bioavailability, and resulting biotin status are crucial in determining whether biotin deficiency is teratogenic in humans. Accuracy in estimating dietary biotin is limited both by data gaps in food composition tables and by inaccuracies in published data. The present study applied sensitive and specific analytical techniques to determine values for biotin content in a select group of foods. Total biotin content of 87 foods was determined using acid hydrolysis and the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 9 publications
0
64
1
Order By: Relevance
“…A detailed investigation of all these influences is very difficult and not feasible during routine analysis when dealing with samples of unknown composition. Recently, published work using a more specific detection technique (HPLC/avidin binding) [4] indicates that many literature values for the biotin content of food may have to be reinvestigated using a method as the described. The microbiological assay is also time-consuming, as it involves incubation of the test organism with the sample extract for 19 h.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed investigation of all these influences is very difficult and not feasible during routine analysis when dealing with samples of unknown composition. Recently, published work using a more specific detection technique (HPLC/avidin binding) [4] indicates that many literature values for the biotin content of food may have to be reinvestigated using a method as the described. The microbiological assay is also time-consuming, as it involves incubation of the test organism with the sample extract for 19 h.…”
Section: Introductionmentioning
confidence: 99%
“…The physical properties of biotin, e.g., the absence of a chromophor suitable for sensitive UV detection, and a high polarity of the molecule making it unsuitable for GC analysis, complicate the analysis in low concentrations. Published alternative methods include HPLC with fluorescence detection after post-column derivatisation [5], HPLC-MS [6,7], and various assays based on protein-binding, mainly using the strong biotin-avidin interaction [4,[8][9][10][11][12]. In our laboratory, a microbiological assay [3] has been applied routinely for more than three decades.…”
Section: Introductionmentioning
confidence: 99%
“…Dose-response relationships between biotin intakes and these biomarkers have not been established. Staggs et al (2004) compared the biotin content of 87 foods measured by HPLC/avidin-binding assay to values published from earlier analyses, mostly using bioassays. This study confirmed previous assessments that meat, fish, poultry, egg, some cheeses and some vegetables are rich dietary sources of biotin.…”
Section: Biomarkersmentioning
confidence: 99%
“…, nitrite NO 2 -and nitrate NO 3 -were checked on a weekly basis. At the end of the study, water samples were collected from the sump and the tape of the recirculating aquaculture system (RAS) for total avidin binding substances (TABS) measurement in water (Mock et al 1995(Mock et al , 1997Staggs et al 2004). Suspended solids were removed using a sand filter, and effluent ammonia was reduced using a trickling biofilter; ammonia and nitrite concentrations were monitored twice weekly to assess biofilter performance.…”
Section: Fish Rearing Conditionsmentioning
confidence: 99%
“…This light yellow aqueous extract layer was diluted by 50-fold, and TABS were measured by competitive enzyme-linked immunosorbent assay (ELISA) (Mock et al 1997). Whole-body fish biotin content was determined according to the procedure developed by Mock et al (1997) as described by Staggs et al (2004). Briefly, the fish was first homogenized with Teflon homogenizer, followed by acid hydrolysis to release protein-bound biotin (Mock and Malik 1992;.…”
Section: Analytical Proceduresmentioning
confidence: 99%